Assessing the nutritional value, fermentation quality, and in vitro degradability of mulberry pomace silage ensiled with sumac additive - Seven, Pinar Tatli; Cicek, Miray Sila; Mutlu, Seda Iflazoglu; Dadan, Furkan Melih; Aktas, Numan Yusuf (Univ Zulia, Facultad Ciencias Veterinarias, 2025)
This study investigates the effects of sumac addition on the nutrient composition, in vitro degradability, and fermentation quality of mulberry pomace silage. Mulberry pomace is rich in protein, making it a valuable feed resource for livestock production. However, its high protein content may lead to increased proteolysis during silage fermentation, resulting in elevated pH levels and undesirable butyric acid production. Sumac, which is rich in tannins and organic acids, has the potential to inhibit proteolysis and enhance the fermentation process, thereby improving silage quality. Therefore, investigating the effects of sumac addition on the nutritional composition and fermentation characteristics of mulberry pomace silage is of significant importance. Mulberry pomace was ensiled in vacuum-sealed jars as an untreated control group (M) and in triplicate with the following treatments: 5% sumac group (MS-5) and 10% sumac group (MS-10). The silos (n=18) were stored for 45 days. After the ensiling period, the jars were opened, and physical and chemical analyses were conducted on the silage samples. The addition of sumac to mulberry pomace silage had a significant effect on dry matter (DM) content (P < 0.001), with the highest DM level observed in the silage group containing 10% sumac. Sumac addition (10%) increased the crude protein content (12.96%) (P < 0.05) while decreasing pH (3.69) and ammonia nitrogen (3.85%) levels (P < 0.05). Compared to the control group, the levels of neutral detergent fiber (23.92%) (P < 0.01), acid detergent fiber (15.41%) (P < 0.05), and acid detergent lignin (7.24%) (P < 0.05) were significantly lower in the 10% sumac group. In conclusion, the addition of sumac to mulberry pomace silage positively enhanced silage quality, contributing to improved fermentation by inhibiting proteolysis due to its tannin content.
Evaluación del valor nutricional, la calidad de la fermentación y la degradabilidad in vitro del ensilaje de orujo de morera ensilado con aditivo de zumaque
Keywords: Morus alba L.; silage; sumac; proteolysis degradability; fermentation